Konflik Batin Tokoh “Aku” dalam Novel Garis Waktu Karya Fiersa Besari - Rumadi, Hadi; Syafrial; Fajriani, Sri Wulan (GERAM: Gerakan Aktif Menulis, 2020)
The inner conflict is a part of the prosaic objectivity elements that are inherent in the characters, especially novels. It occurs as the attraction of the story so that the values ​​of ethics and personal values ​​are illustrated that can be enjoyed. Internal conflict as a reflection of the fact of humanity that is always faced by anyone, does not rule out the possibility of figures contained in literary works. With its existence makes the story more alive and meaningful with all events in it. The focus of inner conflict in this novel is the perspective of the first person 'I', the author of the novel himself, Fiersa Besari. So, this study aimed to describe the inner conflict on the character "I" in Garis Waktu novel written by Fiersa Besari. It was a qualitative study that used a descriptive-analytical method. Garis Waktu Novel was used as a source of data. Identification, description analysis, discussion, and conclusions were applied to analyze the data. The results were the personal life of the character 'I' through psychoanalytic studies. His personal life did not merely apply because of the personality concept as a writer, all the inner conflicts that occurred also related to the social external concepts of characters, where there was an involvement of other people in creating inner conflicts within the character. The conclusion is the inner conflict faced which is a form of emotional overflow that occurs because the elements in themselves are influenced by external elements, so as a character often this inner conflict is a part of personality that cannot be avoided by humans themselves, including the figure of Fiersa Besari.